The Voice of the Oppressed: Representation and Resistance in the Works of Arjun Dangle - Kesari Kumari; Dr. Rakesh Kumar (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This research paper analyzes the thematic and political representations in the literary works and editorial contributions of Arjun Dangle, a pivotal figure in the Dalit Panther movement and Dalit literature. It specifically investigates the depiction of Dalit men as victims of caste exploitation, the intersectional matrix of caste, class, and gender in his narratives, and the emergence of protest and political consciousness as pathways to dignity. Dangle's works, particularly his editorship of the seminal anthology Poisoned Bread, are shown to foreground the systematic humiliation, economic deprivation, and structural oppression faced by Dalits in post-independence India. The study highlights how Dangle moves beyond simple victimhood, transforming personal trauma into collective resistance and reclaiming a new, assertive Dalit identity and masculinity. Furthermore, it examines his nuanced approach to women's voices, acknowledging their enforced silence while simultaneously amplifying their defiance as a critical element of the Dalit struggle.
Keywords: Arjun Dangle; Dalit Literature; Resistance; Oppressed; Critical Concepts; Testimony; Political Anger; Patriarchy; Caste Oppression